Mystical Art Gallery - S Sujendran, Heshandri; Hannani Aman (Applied Information Technology And Computer Science, 2022)
Mystical Art Gallery is a platform that lets multiple artists and potential buyers communicate regarding the art that has been showcased. The objectives of this system are to to design a art gallery website system using PHP, MySQL and html, to develop art gallery website system using VisualStudioCode, Xampp and Brackets, validate the developed system with functional testing. The case study location for this system is internationally to build this system and the system would be accessible worldwide. The artist will update the listings, art prices, achievement articles, availability of art pieces, biography and manage messages from users to get in touch.